Dynamics of sediment phosphorus in the brackish Gulf of Finland - Lehtoranta, Jouni (Finnish Environment Institute, 2013)
One of the main threats facing the Baltic Sea is eutrophication due to an excess supply of nutrients. In the Gulf of Finland, primary productivity and biomasses of autotrophic and heterotrophic organisms are among the highest in the Baltic. The high biomasses are attributed mainly to the eutrophying effects of the large land-derived nutrient inflow from St. Petersburg and via the River Neva. The role of sediment phosphorus (P) in eutrophication is, however, poorly understood in the Gulf. The aim of this study was to obtain information on the regional levels of sediment P and to specify the pools of P. Efforts were also made to define the sediment retention ability of P along the estuarine gradient, to establish the factors that affect the benthic fl ux of P and to assess whether sulphur (S) is a significant factor in sediment P cycling. On the basis of the results it was possible to quantify and consider the ecological implications of the benthic flux of P.The sediments of the Gulf are rich in organic matter, nitrogen (N) and P. A large portion of the mobile pool of P in these sediments consists of iron (Fe)-bound P, which is released when Fe(III) oxides are reduced under anoxic conditions. The increase in the sediment organic matter concentration along the estuarine gradient seems to impair the sediments’ ability to retain P. The highest benthic P efflux was measured in summer and the lowest in winter. The decrease in the near-bottom oxygen concentration in summer may favour anaerobic sulphate reduction followed by iron sulphide (FeS) formation close to the sediment- water interface. In the sediment, the key role in preventing P from entering the water is played by the binding ability of P related to diffusing Fe. In the brackish Baltic Sea, in contrast to most lake systems, the diffusion of Fe may be inactivated by FeS formation. Thus, high effluxes of P to oxic water were measured on bottoms where black sediment indicating the presence of FeS extended to the surface of the sediment.The P released from the ...